Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.jmwh.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Midwives' Knowledge, Perceptions, Beliefs, and Practice Supports Regarding Tobacco Dependence Treatment

Abstract: Clinical practice guidelines and evidence-based reviews confirm the efficacy of tobacco dependence treatment for pregnant women. The purpose of this study was to examine tobacco dependence treatment practices among certified nurse-midwives who treat pregnant women who smoke. Midwives were surveyed to determine knowledge, perceptions, and beliefs about tobacco cessation treatment and to identify practice environmental factors that support treatment practices. Half of all midwives had not heard of the US Public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 33 publications
4
52
0
Order By: Relevance
“…Respondents identified that for half or more of the pregnant women they see, during routine prenatal care visits, 56% "Assist" with the quitting process and 52% "Arrange" follow-up support. This finding is consistent with other studies exploring health care providers' counselling practices for pregnant smokers in Canada and the United States [18,26,27]. Despite having evidence-based best practice guidelines for smoking cessation for more than a decade, the rate of guideline implementation is sub-optimal.…”
Section: Discussionsupporting
confidence: 88%
“…Respondents identified that for half or more of the pregnant women they see, during routine prenatal care visits, 56% "Assist" with the quitting process and 52% "Arrange" follow-up support. This finding is consistent with other studies exploring health care providers' counselling practices for pregnant smokers in Canada and the United States [18,26,27]. Despite having evidence-based best practice guidelines for smoking cessation for more than a decade, the rate of guideline implementation is sub-optimal.…”
Section: Discussionsupporting
confidence: 88%
“…Conventionally, such deficits are addressed by training. But unlike many aspects of clinical care, smoking in pregnancy training opportunities appeared to be limited and non‐mandatory for our participants, as reported elsewhere (Abatemarco et al ., 2007; Flemming et al ., 2016). Non‐mandatory training may influence professional beliefs about the relative importance of smoking in pregnancy compared to other risk factors for which training is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent focus on tackling obesity in pregnancy appeared to reduce the perceived priority of smoking among antenatal professionals. Low prioritization of smoking cessation has been identified previously as a barrier (Abatemarco et al ., 2007; Colomar et al ., 2015), and our findings provide new insight into how priorities may be affected inadvertently by new initiatives targeting other health behaviours. Many parallels with smoking in pregnancy can be drawn with midwives’ experience of discussing obesity with pregnant women and referring them to weight management services (Atkinson, French, Ménage, & Olander, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations